Fancy Nancy And The Too-Loose Tooth - O'Connor, Jane; Preiss-Glasser, Robin; Enik, Ted (New York : Harper, 2012)
Nancy is about to lose her first tooth, but if she can prevent it from falling out until she arrives at school she will get a special necklace from the nurse.
Ages 4-8.
Keywords: Schools -- Fiction; Teeth -- Fiction; Vocabulary -- Fiction; Teeth -- Fiction; Vocabulary -- Fiction; School stories